(3GdeWGdH GdeXaQjI aj QSGdI GdLYaQjIs - (3GdehShj, GdGSJQGHGOj, eMeO Hf CHj WGdH, J (B940 (3g`s ((3eMeO Hf TGg eQGOs)
(3ChdgG (B:s
(3GdMeO ddg GdPj aVdfG Ydi SGFQ GdCee(B... (3CeG HYO aEfj deG CeYfJ fXQj hUQaJ acQj (B... (3aj eWGdYI GdeNJUQ GdehShe(B... (3GdehVhYI aj HGH GdUdGI heG jJYdb HgG(B...s
(3BNQgG (B:s
(3hjbQC BjI GdcQSj SHYG Ke jUdj KeGf QcYGJ HJSdjeJjf JbQC aj cd QcYI GdMeO eQI(B... (3hHGbj GdUdhGJ GdefOhHI ePchQI aj GdcJH GdeWhdI (B...s
(3GdJhKjbGJ GdeQLYjI (B:s
(3eYLe GdeDdajf(B: (3L(B3(3, U(B362s
(3GdPQjYI HQbe(B: 4326s
(3GdPQjYI HQbe(B: 4326s
(3EjVGM Gdecfhf(B: (3L(B2(3, U(B49s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3abg GdePGgH GdCNQis